Impacts of Vegetation Changes on Land Evapotranspiration in China During 1982–2015 - MingYue, Zhan; Guojie, Wang; Hagan, Daniel Fiifi Tawia; Waheed, Ullah; Giri, Kattel; Jiao, Lu; ShiJie, Li (Frontiers in Environmental Science, 2022)
Evapotranspiration (ET) bridges the hydrological and energy cycle through vegetation transpiration (T), soil evaporation (ES), and canopy interception evaporation (EI). Transpiration to evapotranspiration ratio (T/ET) quantifies the water use efficiency of terrestrial ecosystems explaining the mechanism of vegetation water transport and water-carbon interactions. This study employed GIMMS LAI3g data to improve the CLM4.5 land surface scheme of RegCM4.6. We designed two simulation experiments, each with control (CTL) and sensitivity (SEN), simulating the interannual variability of vegetation on ET and T/ET in China from 1982 to 2015. Studies show China has experienced a greening trend, especially in the mid-south China and South China. Leaf area index (LAI) increased significantly (0.002m2m-2yr-1). ∆LAI ( SEN input LAI data minus CTL input LAI data) and ∆T/ET ( T/ET data output by SEN minus T/ET data output by CTL ) have shown significant positive correlations. The impacts of LAI on T/ET are more prominent during spring and winter than in autumn and summer. Compared with T/ET and LAI (R=0.70), the correlation between ET and LAI is moderate (R<0.5), indicating that vegetation has a higher impact on T/ET than ET. The impact of vegetation anomalies (positive and negative LAI anomalies) on T/ET and ET is spatially different, mainly due to dominant factors affecting ET and T/ET changes. In spring, summer and autumn, &T (Transpiration changes corresponding to vegetation anomalies) is the leading factor affecting both ET and T/ET regionally, and &T has a stronger influence on T/ET than ET, especially in summer. Vegetation anomalies have a stronger influence on T/ET than ET; and the influence of positive vegetation anomalies on ET and T/ET is greater than negative vegetation anomalies, especially in spring and autumn. This study reveals the mechanisms behind vegetation processes and influences on the water and heat fluxes at the land-atmosphere interface and provides a strong scientific basis for studying the water cycle under climate warming.